The Effects of Projects Based Chemistry Learning Model, Assisted by Chemsong Video to Students’s Learning Completeness and Creativity (Universitas Negeri Semarang, 2020)
This study aims to examine the effect of project-based chemistry learning models on cearning completeness and student creativity through the Chemsong video making project. The research method uses the pretest-posttest control group design while the data analysis uses the parametric statistical test that is N-gain, the independent sample t test and the sample t-test paired test. The sample in this study was obtained by cluster random sampling technique from the population of all students of SMK N 8. The gain normality test showed that the average results of the pretest-posttest clasical learning completeness increased by 0.53 with the criteria being in the experimental class and the control class at 0,31 with moderate criteria. The results of the independent sample t-test showed that there was a significant difference in the classical learning completeness of the experimental and control group students, which was 4.56 greater than t critic 1.98 with a significance level of 5%. In the paired sample t test, the value of sig. (2-tailed) of 0,000 <0.05. Whereas the results of student creativity t-test obtained sig values. (2-tailed) of 0,000 <0.05. So it can be concluded that the application of the chemistry learning model based on the Chemsong video project has an effect on improving student mastery learning and creativity.